2000
DOI: 10.1161/01.atv.20.8.1921
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenicity of Thermolabile Methylenetetrahydrofolate Reductase for Vascular Dementia

Abstract: Abstract-Although the major biochemical abnormality due to methylenetetrahydrofolate reductase (MTHFR) deficiency is hyperhomocyst(e)inemia, its pathogenicity appears to involve more than homocysteine toxicity. In patients with severe MTHFR deficiency, a metabolite(s) other than hyperhomocyst(e)inemia also appears to be associated with its clinical manifestation in cerebrovascular disease. To elucidate the specific role of the TT genotype of MTHFR in the development of cerebral infarction with and without cogn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
1
1

Year Published

2002
2002
2009
2009

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 25 publications
3
42
1
1
Order By: Relevance
“…26 -56 Only 2 studies reported crude ORs for ischemic stroke associated with TT and CT genotypes. 40,42 Crude ORs were recalculated in the remaining studies because (a) no OR provided in original publication (14 studies) † (b) adjusted but not crude OR provided (5 studies) 41,45,47,53,54 (c) risk was calculated only for TT genotype compared with a combined CTϩCC group (6 studies) 26,30,31,33,43,46 (d) subgroups with imaging-proven intracerebral hemorrhage included so ORs specific for IS calculated (4 studies). 37,48,52,56 One study 36 reported OR separately for white and black ethnicities-these were included separately, making a total of 32 study samples in the overall analysis (Table).…”
Section: Search Resultsmentioning
confidence: 99%
“…26 -56 Only 2 studies reported crude ORs for ischemic stroke associated with TT and CT genotypes. 40,42 Crude ORs were recalculated in the remaining studies because (a) no OR provided in original publication (14 studies) † (b) adjusted but not crude OR provided (5 studies) 41,45,47,53,54 (c) risk was calculated only for TT genotype compared with a combined CTϩCC group (6 studies) 26,30,31,33,43,46 (d) subgroups with imaging-proven intracerebral hemorrhage included so ORs specific for IS calculated (4 studies). 37,48,52,56 One study 36 reported OR separately for white and black ethnicities-these were included separately, making a total of 32 study samples in the overall analysis (Table).…”
Section: Search Resultsmentioning
confidence: 99%
“…The frequency of TT genotype in younger NTG patients in our study (38.9%) is much higher when it is compared with the results reported in different ethnic populations (2-17.9%). 10,13,14,16,[22][23][24][25][26][27][28][29] Genetic traits of a disease should be more important in younger patients than in older ones. If one has a genetic predisposition to a disease, it is likely that the disease should develop earlier.…”
Section: Discussionmentioning
confidence: 99%
“…TT genotype has been proven to be associated with vascular diseases such as cardiovascular and cerebrovascular diseases. 10,[13][14][15][16] Another MTHFR gene polymorphism of 1298A4C was reported to be associated with lower blood folate levels and higher blood homocysteine levels in some studies. 17 MTHFR gene polymorphism and resultant hyperhomocysteinaemia as a risk factor of vascular diseases prompted us to investigate the association between MTHFR gene polymorphism and NTG.…”
Section: Introductionmentioning
confidence: 99%
“…17,25 Although we did not analyze cognitive function in the present study, an association between impaired cognitive function and SBI and white matter lesions has also been reported. 14,22 In several studies, the MTHFR TT genotype has also been demonstrated to be a risk factor for dementia, 26,27 although conflicting results have also been reported. 28,29 These findings suggest a possible association between the MTHFR TT genotype and cognitive impairment in the general population.…”
Section: Kohara Et Al Mthfr Gene and Silent Brain Infarctsmentioning
confidence: 99%